2017
DOI: 10.1177/0748233717733853
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for non-fatal occupational injuries among construction workers: A case–control study

Abstract: Cannabis abuse can increase injury severity and prolong workdays lost. Drug testing is recommended for at-risk construction workers with inadequate safety measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…This table shows the characteristics of our sample mainly the age that ranging from (33-51) that reflect the reproductive age in our society with such qualifications that met such work. This outcome is consistent with studies (11,12) . In relation to residency area, the majority of workers (73.6 %) were from urban.…”
Section: Discussionsupporting
confidence: 93%
“…This table shows the characteristics of our sample mainly the age that ranging from (33-51) that reflect the reproductive age in our society with such qualifications that met such work. This outcome is consistent with studies (11,12) . In relation to residency area, the majority of workers (73.6 %) were from urban.…”
Section: Discussionsupporting
confidence: 93%
“…IT sector employees are exposed to a range of psychosocial hazards which include, but are not limited to, low levels of management support, high workload (time pressures and overall job demands) and low job control. In contrast, the mining and construction sectors (included in the materials sector) have high injury and accident rates and also face public scrutiny in relation to the activities undertaken to mitigate these risks (Khashaba et al 2018;Nowrouzi-Kia et al 2018). In line with stakeholder theory, this scrutiny places obligations on organisations to develop and implement appropriate prevention actions, which can then be publicized to positively promote their reputation, as previously suggested by others (Roca and Searcy 2012;Chen and Zorigt 2013;Tsalis et al 2018).…”
Section: Discussionmentioning
confidence: 96%
“…The impacts of this on road crashes and workplace accidents are explored in Chapter 8 and Section 6.3.1, respectively, however there is also the potential for excess rates of other forms of accidental injury such as vehicle crashes that do not occur on the road, falls, burns and scalds, drowning, and sharp object injuries. At present, whilst case studies have identified a role for cannabis in increasing risk (Khashaba et al, 2017;Wadsworth et al, 2006), there are no reliable estimates of the extent to which cannabis contributes to excess rates of these forms of injury in Australian workplaces. As such they were not included in our calculations.…”
Section: Limitations 6521 Accidentsmentioning
confidence: 97%